Faktor Determinan yang Berpengaruh Terhadap Status Gizi Remaja - Detrina Friskadian Uramako (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: The youth group as a determinant of the quality of human resources, carries the baton in continuing the nation's development so that adolescents need to get attention in terms of health and nutrition. The purpose of analyzing the determinant factors that affect the nutritional status of adolescents. Method; This research uses quantitative. Data collection techniques through the distribution of questionnaires as an instrument of probability sampling technique. Univariate, bivariate, and multiple linear regression analysis. Results; show the factors that most influence the nutritional status of adolescent knowledge with a B value of 0.558. Conclusion; that there is a significant influence between knowledge of nutrition, diet, food ingredients, and family support on nutritional status.